Radon an indoor risk: In the Urban Devarakonda, Telangana state, India - M. Srinivas Reddy; G. Suman; K. Vinay Kumar Reddy; M. Sreenath Reddy; Ch Gopal Reddy; P. Yadagiri Reddy (Nuclear Engineering and Technology)
Natural background radiation risk owing to radon and its progeny at indoors to the general public is a significant issue. The concern about indoor radon risk has been increasing at national and international level since its role to the overall dose is well known. The current study aims to assess the 222Rn and its progeny in different type of indoors with a passive (SSNTD) and active technique (RAD-7). The area of investigation (urban Devarakonda), is located near the proposed uranium mineralization area. The estimated radon levels in the indoors were ranging from 20 to 437 Bq. m−3 and with a geometric mean of 66 Bq.m−3. The estimated EERC values are ranging from 22 to 82 Bq.m−3 and these are higher than the range limit prescribed by ICRP. The computed average EF value in the present study (0.58) is relatively higher than the world average value of 0.4. An effort has been made to comprehend the radon distribution among the representative locations. Annual effective inhalation dose was also estimated using the occupancy factor 0.8 and it is found in the range of 0.52–11.00 m Sv y−1 with geometric mean of 2.20 mSv.y−1. The diurnal variation of 222Rn levels was studied using RAD-7 in a dwelling and seasonal variation of radon levels was also to be discussed in this paper.